Radical cascade cyclization of unactivated alkene-tethered indoles with aryldiazonium salt and sodium metabisulfite to access Azo- and Sulfonylated-2,3-Dihyro-1H-pyrrolo[1,2-a]indoles - Kumar, Pawan; Rai, Archana; Kumar, Manish; Krishna, Gamidi Rama; Das, Utpal (Journal of Organic Chemistry, 2023)
A method for the construction ofheterocyclic scaffold2,3-dihyro-1H-pyrrolo[1,2-a]indolesvia arylsulfonylradical-triggered cascade cyclization of unactivated alkene-tetheredindoles in the absence of any external photocatalyst has been developed.This protocol features easily accessible starting materials such assodium metabisulfite and aryldiazonium tetrafluoroborates at roomtemperature and offers good functional group compatibility, enablingthe introduction of various functionalized sulfonyl and azo groupsinto pyrrolo[1,2-a]indoles.

Accessing meta -enone-substituted anisoles using ArN 2 BF 4 as precatalyst via rearrangement of alkyne-tethered cyclohexadienones - Rai, Archana; Das, Utpal (Synthesis-Stuttgart, 2024)
Keywords: alkyne-tethered cyclohexadienone; diazonium salt; rearrangement; substituted anisoles

Reaction of 4 (Alkynyloxy)cyclohexa-2,5-dienones with Dimethyl Sulfoxide: a catalyst-free formation of 6/5/3-fused tricyclic enones - Rai, Archana; Das, Utpal (Journal of Organic Chemistry, 2024)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">6/5/3-Fused tricyclic enones were obtained when 4-(alkynyloxy)cyclohexa-2,5-dienones were treated with DMSO at 150 °C. The reaction proceeded via a four-membered oxathietene intermediate. The protocol developed is atom economical, has a broad substrate scope, and is amenable to gram-scale synthesis. The products obtained are susceptible to further synthetic transformations.

Ipso-cyclization via a dienone-phenol rearrangement of alkynyloxy cyclohexadienones for the synthesis of oxaspiro[4.5]trienones - Rai, Archana; Kundu, Ananya I.; Shukla, Ekta; Das, Utpal (Journal of Organic Chemistry, 2025)
Herein, we present a convenient method to access oxaspiro[4.5]trienone compounds from alkynyloxy cyclohexadienones. The reactions are catalyzed by Lewis/Bronsted acids, yielding the desired products in moderate to good yields under very mild reaction conditions. The process, which involves a dienone-phenol rearrangement, is characterized by its simplicity and the absence of any additional activators. The synthesis of the oxaspiro[4.5]trienone compounds is amenable to gram-scale reactions along with subsequent product transformations, making this approach practical and attractive.

Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.

Zn(ii)-metallo-photoantibiotics: experimental and computational approach identifying a therapeutic role for antibacterial and antibiofilm applications - Kushwaha, Rajesh; Kumari, Sangeeta; Mishra, Arya; Upadhyay, Anjali; Rai, Archana; Nayak, Malay; Mukherjee, Sudip; Banerjee, Samya (Chemical Communications, 2025)
The antibacterial profiles of curcumin-based novel Zn(ii)-metallo-photoantibiotics against E. coli and B. subtilis are reported. In silico studies indicated their ROS generation capacity and binding interaction with bacterial proteins. Therapeutic results indicated the advantages of these Zn(ii)-metallo-photoantibiotics in antibacterial photodynamic therapy.